Genetic Polymorphism of the Angiotensin-Converting Enzyme in Bronchial Asthma - Marushchak, Mariya; Krynytska, Inna; Tokarskyy, Oleksandr; Koval, Mariya; Demianchuk, Mykhailo (Bangladesh Journal of Medical Science, 2022)
Background: Bronchial asthma (BA) is among the most prevalent chronic inflammatory disorders of the lung airways, and it has become clear that a combination of genetic predisposition and environmental factors plays a critical role in its pathogenesis. Objective: The correlation of the angiotensin-converting enzyme (ACE) insertion/deletion polymorphism and other factors with risk for bronchial asthma development was assessed. Materials and Methods: Online literature search was conducted to identify the most relevant studies. Results and Discussion: The ACE insertion/deletion (I/D) gene polymorphism, correlating with cellular and circulating ACE concentration, may play a critical role in BA pathogenesis and has been a focus of numerous epidemiologic studies; however, the results are currently inconclusive. The contradictions in the literature between research groups on the role of ACE alleles and genotypes can be explained by genetic variation and multifactorial causes of BA. Conclusion: This literature review demonstrates that the ACE I/D polymorphism might be related to the risk of bronchial asthma and can become a useful tool in designing effective treatment approaches. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 492-501